(-6)•(-2)²-(-3)•[(-7)•(-2)+(-8)²-(-1)]:(-1)
Răspunsuri la întrebare
Răspuns de
2
(-6)•(-2)²-(-3)•[(-7)•(-2)+(-8)²-(-1)]:(-1) = -6·4+3(14 +64 +1) :(-1) =
= -24 +3·79 : (-1) = -24 - 237 = - 261.
Răspuns de
1
... = (-6)·(+4) - (-3)·[+14 + 64 + 1]:(-1) =
= (-24) + 3·(+79):(-1) =
= - 24 + 3 · (- 79) =
= - 24 - 237 =
= - 261
= (-24) + 3·(+79):(-1) =
= - 24 + 3 · (- 79) =
= - 24 - 237 =
= - 261
Alte întrebări interesante
Franceza,
8 ani în urmă
Biologie,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă